Upaya Peningkatan Literasi Digital Masyarakat Desa Tanjung Medan - Budianto Bangun; Mulkan Ritonga; Rahma Muti’ah; Syahrol Sulaiman (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2022)
Through digital literacy in order to improve knowledge, by carrying out community service, it plays an important role with training on efforts to improve community digital literacy which was carried out in Tanjung Medan village, with participants who were followed by the community and Tanjung Medan village officials. raised the title of service, namely "Efforts to Improve Digital Literacy Tanjung Medan Village Community". In delivery of the material presented is very good. Before carrying out the information technology knowledge training activity, a test was held, it turned out that it was known that those who did not know how to use information technology The use of the internet with the aim of serving the community in Tanjung Medan village was very positively responded and brought transformation to residents of Tanjung Medan village. The information technology digital literacy knowledge training on the internet was carried out Post-Test at the presentation material by community service team by lecturers and students at Labuhanbatu University. other factors, such as the unavailability of infrastructure during the training, and the different abilities of participants, it is necessary to try training and education on using the internet for residents of Tanjung Medan Village in the future.Keyword: digital literacy; improvement efforts; tanjung medan village